2017
DOI: 10.14687/jhs.v14i2.4133
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the heart rate and oxygen saturation values of u13 category footballers at competition occasion who stand in different Uphill cities<p>Farklı yükseltideki illerde bulunan u13 kategorisi futbolcuların müsabaka ortamında nabız ve oksijen saturasyon değerlerinin incelenmesi

Abstract: The aim of this study is to investigate the heart rate and oxygen saturation values of U13 footballers at competition occasion who stand in different cities. 34 footballers participated to the study totally who are playing U13 teams of Ankara Keçiören Bağlum Sport Club and Isparta Iyaş Youth and Sport Club. Height, weight, heart rate and oxygen saturation measurements were taken from research groups. In analyzing handled datas, Independent t Test was used at SPSS 18.0 for Windows. Research Groups’ height means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In another study, it was found that SPO 2 saturation of Ankara Baglum Sports Club players decreasrd little by little at 10th, 20th, 30th and 40th minute of competition, while the SPO 2 saturation of Isparta Iyas Youth and Sports club players raised at beginning, 10th, 20th, 30th, 40th minute of competition (Bagis & Kumartasli, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…In another study, it was found that SPO 2 saturation of Ankara Baglum Sports Club players decreasrd little by little at 10th, 20th, 30th and 40th minute of competition, while the SPO 2 saturation of Isparta Iyas Youth and Sports club players raised at beginning, 10th, 20th, 30th, 40th minute of competition (Bagis & Kumartasli, 2017).…”
Section: Discussionmentioning
confidence: 91%